Analgesic efficacy of a portable, disposable, and self-applied transcutaneous electrical nerve stimulation device during migraine attacks: A real-life randomized controlled trial - Domingues, Flávia S. [UNESP]; Gayoso, Maisa V. [UNESP]; Sikandar, Shafaq; da Silva, Leopoldo Muniz; Fonseca, Ronaldo G. [UNESP]; de Barros, Guilherme A. M. [UNESP] (Wiley, 2021)
Objective: The objective of this study was to evaluate the analgesic efficacy of a portable, disposable, and home self-applied transcutaneous electrical nerve stimulation (TENS) device during migraine attacks. Background: TENS has been used as a noninvasive treatment for migraine, but there are no reports on the outcomes following use of this treatment option for use at home during migraine attacks. Design and Methods: A double-blind, randomized controlled trial was conducted over 3 months, with monthly assessments. Active placebos (sham group) were in place and were allocated at a 1:1 ratio. Adult patients who had been diagnosed with migraine by a specialist were included. Pain intensity levels and functional disability were measured before and after the 20-min self-applied TENS intervention during the migraine attacks. Results: Seventy-four participants were randomly allocated to the sham and intervention groups. Although both groups of subjects reported lower pain scores, the intervention group showed a statistically significant reduction in pain scores compared to the sham group. Conclusion: In our controlled trial, the use of a self-applied, TENS device is safe and effective in relieving pain associated with migraine attacks. Participants in the intervention group showed a statistically significant improvement in pain and functional disability scores. TENS has been used as a noninvasive treatment for migraine, but there are no reports on the outcomes following use of this treatment option for use at home during migraine attacks. This double-blind, randomized controlled trial had 2 groups: active-placebo and intervention. Seventy-four participants were randomly allocated. Participants in the intervention group showed a statistically significant improvement in pain and functional disability scores.
Keywords: headache; migraine; transcutaneous electrical nerve stimulation (TENS)